Development of sera makarya technology (automatic watering system using solar cells) as a food security improvement for bean sprouts in Sleman - Raya, Desta Lintang Handa; Gibran, Fabian Khalid; Saputro, Yuli; Saputro, Handoyo; Sebastian, Rio (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2024)
Dusun Gamelan in Sleman, an area with significant agricultural potential, faces challenges in food security, particularly in bean sprout production. To address these challenges, this study aims to develop the SERA MAKARYA technology (Automatic Watering System Using Solar Cells) based on Arduino Nano, which can enhance food security for bean sprouts in the region. This is a Research and Development study involving two expert validators from the agricultural sector, namely an agricultural lecturer and the agricultural service office. The research instruments cover four assessment aspects: design, performance, reliability, and innovation, along with feedback from the validators. Data analysis was conducted using descriptive statistics. The results show that the SERA MAKARYA technology received a feasibility rating of 4.40 (very good) in the design aspect, 3.70 (good) in performance, 4.00 (good) in reliability, and 4.40 (very good) in innovation. The novelty of this research lies in the integration of Arduino Nano technology with a solar power system, which has not been widely applied locally in automatic watering technology for bean sprouts. Thus, this technology is deemed feasible for implementation in Dusun Gamelan and has the potential to support sustainable food security improvements. The use of Arduino Nano integrated with solar power in the automatic watering system is a new innovation in the local agricultural sector, particularly in bean sprout production, offering an efficient and sustainable solution.